COVID-19 and Lifestyle Changes: A Cross-Sectional Study at Primary Care Settings in Dubai - Alia M.H.D. Waleed Al Sakkal; Alia Juma AlFalasi; Mouza Khalifa Mohd Saeed AlMehairi; Heba Ahmed Reda Hassan Mohamed; Jawad Ahmad Khan; Imad Saaid Dabbous (Dubai Medical Journal)
Introduction: The first report on COVID-19 was in Wuhan, Hubei Province, China on December 31, 2019. COVID-19 was declared a pandemic by the World Health Organization on March 11, 2020. As a result of the COVID-19 pandemic, the world had to adopt certain modifications to hinder the transmission of the disease. These changes have affected patients’ sleeping, dietary, and lifestyle habits. Little research is conducted on these changes among patients presenting at primary healthcare settings following the pandemic. Therefore, we conducted this study to determine the self-reported changes in these habits in patients attending primary health care centers of Dubai both before and during the pandemic. Material and Methods: A cross-sectional study was conducted among patients attending primary health care centers in Dubai from November 2020 to August 2021. Patients filled out an online questionnaire that included items for sociodemographic characteristics and study outcomes. The outcomes included changes in sleeping, smoking, dietary, and sporting habits both before and during the pandemic. Data were further stratified by gender. Results: A total number of 385 patients participated in this study. Significant changes in sleeping habits both before and during the pandemic were observed among included patients (p = 0.004) which were consistent in female patients only (p = 0.025). Most patients were not smokers both before and during the pandemic (92.98% vs. 92.46%); however, no significant change was noted across male (p = 0.503) and female patients (p = 0.391). There was a positive change in sporting habits across both male (p = 0.005) and female patients (p = 0.001). The majority of patients reported no change in the number of daily meals eaten (50.13%) following the pandemic. Conclusion: Our study highlighted that sleeping habits among primary care patients were negatively affected during the pandemic as compared to before. However, there was a positive change in their sporting habits with no change in smoking. Additionally, no substantial change in dietary habits was noted. However, further research is needed to confirm our findings.